The Impact of E-Commerce On Clothing Traders In Pasar Besar Palangka Raya, Indonesia - Wakhidah, Nur; Sadiani, Sadiani; Sardjuningsih, Sardjuningsih; Nazir, Muhammad (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
The economic transformation towards e-commerce has significantly impacted traditional merchants. This study examines the effects of this phenomenon on the family economy of clothing traders in Pasar Besar, Palangka Raya City, Indonesia. Using a qualitative approach, this research analyzes data from 20 respondents through in-depth interviews and direct observation. The framework uses Karl Max’s economic theory. Results indicate that e-commerce impacts: (1) a decrease in sales turnover by up to 40%, (2) changes in traders' work patterns, and (3) adaptation of marketing strategies to digital platforms. While e-commerce offers better prospects, it also creates economic difficulties for traditional traders' families. These findings provide crucial insights for traders and policymakers in designing effective adaptation strategies and regulations. The study recommends a balanced economic approach, considering social and environmental aspects, in line with the people's economy principle in the 1945 Constitution.